Finding New Ways to Read Digital Talking Books - Carriço, Luís (2009)
In this paper we present new ways to read Digital Talking Books (DTBs). DTBs aim to provide better access to literary contents for the visually impaired population. However, these books offer limited capabilities when reading the book freely. Only continuous reading or jumping through sections of the text is allowed. This lack of flexibility leaves out many of the types of reading users usually do, such as those that provide the user with an overview of the book content or readings based on a specific set of key points that have more importance to the user. The work we present here overcomes these limitations by providing the user with a whole new range of interaction possibilities with DTBs